Implications of the obesity in the climacteric and menopause woman - Nesi, Aline Daniela (2012)
In order to identify the determinant factors of the obesity in the climacteric and menopause, a bibliographic research was done, selecting 14 articles published between 2000 and 2007 and books from 1998. The studies were done with 6500 women around 40 and 65 years old. Among the works analyzed, 8 did not demonstrate relation between obesity and climacteric, neither menopause, 2 positively associated the weight increase with this phase of the woman life. Some studies (2) associated the menopause with the increase of the total and LDL cholesterol levels, and also the reduction of HDL-cholesterol. The weight increase had no relation with the realization (or not) of hormonal reposition therapies. The conclusion was that the overweight and obesity during the climacteric and menopause period is not only influenced by hormonal factors, but also by the life style like the lack of physical activities, hyper caloric and hyper lipid alimentation and smoking habits, besides psychosocial factors. Additional studies need to be done, but according to the analysis developed, the suggestion is to increase the number of educational programs that promote life style improvement, like healthy alimentation habits and regular physical activities.